Testing the theory of planned behaviour in predicting condom use in eastern Ghana : a three-wave longitudinal study - Teye-Kwadjo, Enoch (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2014.